Synthesis of a Functionalized Polymer Based on a Calix[4]resorcinarene via Covalently Anchored Cationic Moieties: A Reactive Solid Support for Ring Transformation and Expansion of Thiopyrylium Salts - Mouradzadegun, Arash; Elahi, Somayeh; Abadast, Fatemeh (Synthesis, 2015)
In this work, for the first time, a cationic polymer containing pendant pyridinium groups was synthesized via post-functionalization of the polymeric backbone based on a calix[4]resorcinarene, and characterized by AFM, TEM, analytical CHN, TGA, and DTG techniques. The functionalized polymer is conveniently loaded with desired anions, thereby providing novel and recyclable polymer-supported reagents for achieving synthetic goals. The thermal stability of this cationic polymer (up to 250 °C by TGA) allows thermally demanding ring transformation and expansion of 2,4,6-triarylthiopyrylium salts on its side chains and polymeric backbone without decomposition and leaching of active species in the reaction media. This green method furnished a straightforward route for the synthesis of valuable 2,4,6-triarylpyridines, along with novel 2,5,7-triaryl-1,3-thiazepine derivatives, which are widely present as motifs in an assortment of biologically active molecules.
Keywords: azide; green chemistry; heterocycles; nucleophilic addition; polymers; ring expansion